A hypoxia efficient imidazole-based Ru(ii) arene anticancer agent resistant to deactivation by glutathione1. Issue 13 (7th April 2015) - Purkait, Kallol; Karmakar, Subhendu; Bhattacharyya, Sudipta; Chatterjee, Saptarshi; Dey, Suman Kr; Mukherjee, Arindam
<x xml:space="preserve">Abstract</x> [RuII(η6-p-cym)(L)Cl](PF6) is slow to hydrolyze and shows better anticancer activity in hypoxia with strong resistance to deactivation by l-glutathione.